Cortical processing of breathing perceptions in the athletic brain - Faull, O; Cox, P; Pattinson, K (Elsevier, 2018)
Athletes regularly endure large increases in ventilation and accompanying perceptions of breathlessness. Whilst breathing perceptions often correlate poorly with objective measures of lung function in both healthy and clinical populations, we have previously demonstrated closer matching between subjective breathlessness and changes in ventilation in endurance athletes, suggesting that athletes may be more accurate during respiratory interoception. To better understand the link between exercise and breathlessness, we sought to identify the mechanisms by which the brain processing of respiratory perception might be optimised in athletes. Twenty endurance athletes and twenty sedentary controls underwent 7 T functional magnetic resonance imaging. Inspiratory resistive loading induced conscious breathing perceptions (breathlessness), and a delayconditioning paradigm was employed to evoke preceding periods of breathlessness-anticipation. Athletes demonstrated anticipatory brain activity that positively correlated with resulting breathing perceptions within key interoceptive areas, such as the thalamus, insula and primary sensorimotor cortices, which was negatively correlated in sedentary controls. Athletes also exhibited altered connectivity between interoceptive attention networks and primary sensorimotor cortex. These functional differences in athletic brains suggest that exercise may alter anticipatory representations of respiratory sensations. Future work may probe whether these brain mechanisms are harnessed when exercise is employed to treat breathlessness within chronic respiratory disease.